PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN PROFITABILITAS TERHADAP MANAJEMEN LABA - Gita Varina Putri; Abdul Rohman (Diponegoro Journal of Accounting, 2016)
The aim of this study is to examine the influence of corporate social responsibility disclosure and profitability on earning management practice. Independent variable used in this study is corporate social responsibility disclosure that measured using CSR Index (CSRI) based on GRI. Beside corporate social responsibility, profitability also independent variable in this study. Dependent variable used in this study is earning management that measured using proxy of earning management 3. Size and leverage also used as control variables. The population in this study consists of all listed firm in Indonesia Stock Exchange in year 2012 - 2014. Sampling method used is purposive sampling. A firm criteria are mining and maufacture at that year which publish sustainability report and also the completed information of financial report. The total sample are 366 firms data. Analysis test using a model of multiple regression. The result of this study show that corporate social responsibility disclosure has a significant influenced and have negatively on earning management. Profitability also has a significant influenct and have positively on earning management.